Blended Course Experience at Jaramogi Oginga Odinga University of Science and Technology - Abeka, Silvance O.; Gwada, Dorothy (Commonwealth of Learning, 2021)
This is the report of a survey conducted at Jaramogi Oginga Odinga University of Science and Technology (JOOUST) to evaluate the implementation of technology-enabled learning. The research was conducted among students and lecturers on courses that were offered in a blended mode. The courses were developed and facilitated by 20 lecturers who had been trained as champions for the implementation of blended learning. Each of the 20 champions was required to set up their blended courses on the eJOOUST platform, which had been customised from Moodle. The blended courses were taught throughout the September–December 2019 semester, and the survey was undertaken in January 2020, after the students had completed their blended courses.